Empathy and Other Mysteries: Neuroscientists are discovering things about the brain that answer questions philosophers have been asking for centuries. - Restak, Richard (American Scholar)
This article discusses the psychological aspects of feelings such as empathy and concepts such as time. It addresses an experiment by psychologist and neuroscientist Lera Borodistky regarding psychological differences between individuals who operate under an ego-moving perspective and those who use a time-moving perspective. The storage and process of spatial and temporal information in the brain is explored. Other topics addressed include the role of simultaneity in brain processes, the relationship between subjectivity and perception, and connections in the ways the brain processes time, space, and the feelings and perspectives of others. The medial prefrontal cortex (MPFC), a section of the brain, is examined for its use in allowing humans to empathize.